A Study of the Hadith on Trust from the Perspective of the Phenomenon of Corruption in Indonesia: A Ma'ani Analysis of Al-Hadith - Bilal Ramadhan; Nasrulloh Nasrulloh (Penerbit Hellow Pustaka, 2025)
This study examines how the concept of amanah in the Prophet’s hadith is understood through the Ma’ani al-Hadith approach and contextualized within the growing phenomenon of corruption in Indonesia. The research is motivated by increasing abuses of power and declining public integrity, which indicate a weak internalization of amanah in socio-political life. Offering theoretical contribution, this study analyzes key hadiths on amanah, including its disappearance as a sign of the Last Day, its association with hypocrisy, and the prohibition of betrayal. These hadiths are examined both textually and contextually and then related to contemporary issues of public ethics and governance. Using a qualitative library-based method, the research focuses on the meaning of amanah, its relevance to corrupt behavior, and its implications for ethical leadership. The findings reveal that amanah plays a vital role in strengthening moral integrity, professional responsibility, and public accountability, which are essential foundations for corruption prevention. The study emphasizes the urgency of reinforcing amanah through religious education, moral development, and institutionalized public ethics in Indonesia.